2021
DOI: 10.1186/s12885-021-08761-0
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening “see and treat approach”: real-life uptake after invitation and associated factors at health facilities in Gondar, Northwest Ethiopia

Abstract: Background Although cervical cancer is a preventable disease, screening coverage in Ethiopia is far below the target. There is limited evidence on uptake among the general population in Ethiopia. Thus, this study was conducted to assess uptake and associated factors with the cervical cancer screening “see and treat approach” among eligible women in public health facilities in Gondar town, Northwest Ethiopia. Method A facility-based, cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…About one-third of our participants reported self-initiating the cervical cancer screening, which is similar to a facility-based study that was conducted in Addis Ababa in 2019 and found self-initiated cervical cancer screening to be 33.3% [ 17 ]. Health literacy, based on education and access to understandable health information, has been shown as one of the key factors for increasing the self-initiation of screening [ 6 , 8 , 9 , 10 , 11 , 12 , 13 ]. What is more, awareness is very important for self-initiated cervical screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About one-third of our participants reported self-initiating the cervical cancer screening, which is similar to a facility-based study that was conducted in Addis Ababa in 2019 and found self-initiated cervical cancer screening to be 33.3% [ 17 ]. Health literacy, based on education and access to understandable health information, has been shown as one of the key factors for increasing the self-initiation of screening [ 6 , 8 , 9 , 10 , 11 , 12 , 13 ]. What is more, awareness is very important for self-initiated cervical screening.…”
Section: Discussionmentioning
confidence: 99%
“…C. Especially due to the related costs and perceived benefits of the private sector, such as shorter waiting times, it can be assumed that the clientele of both sectors differs. Existing studies on cervical cancer screening often focus on public health facilities or it is not identifiable whether the included health facilities are public or private [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence and mortality of CC have been reduced in countries through organized screening programmes [ 10 , 11 ]. In developing countries, including Ethiopia, the CC screening rate is low, ranging between 1 and 23% [ 12 14 ]. Recently, in Ethiopia, CC screening centres are being established to provide screening services for all eligible women.…”
Section: Introductionmentioning
confidence: 99%
“…In Kenya, higher uptake for the Pap test was found among women who had sexual autonomy when compared with their counterparts [ 26 ]. Low educational level, poor knowledge towards cervical cancer and screening, long distance to screening site, fear of positive result, embarrassment was some of the barriers of cervical cancer screening uptake in Ethiopia [ 12 – 15 , 17 – 19 ]. Besides, data from other countries showing that greater sexual autonomy increase uptake [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation